2020
DOI: 10.1177/0218492320977633
|View full text |Cite
|
Sign up to set email alerts
|

Sternal wound infections during the COVID-19 pandemic: an unexpected benefit

Abstract: Background The novel coronavirus, now termed SARS-CoV-2, has had a significant impact on cardiac surgical services globally. Although drastically reduced, our institution has maintained a significant level of cardiac surgical activity during the pandemic. Rigorous COVID-19 guidelines have been instituted to mitigate the risk of viral transmission. We observed a reduction in sternal wound infections since the institution of new perioperative surgical guidelines. Methods We performed a retrospective analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Our results may be congruent with the findings of Unterfrauner et al, that medical centers and surgical procedures with low rates of SSIs pre-COVID-19 may not benefit from additional infection prevention measures of perioperative COVID-19 precautions to the extent seen in centers and surgical procedures with historically higher rates of SSIs. 13 While the aforementioned small, retrospective, singlecentered studies provided hope that SSIs may be reduced early in the pandemic, [9][10][11]18 larger subsequent studies, including the findings herein, fail to demonstrate significant differences. Although counterintuitive, we observed no robust or statistically significant changes in SSI despite unprecedented changes in surgical workflow and PPE use.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our results may be congruent with the findings of Unterfrauner et al, that medical centers and surgical procedures with low rates of SSIs pre-COVID-19 may not benefit from additional infection prevention measures of perioperative COVID-19 precautions to the extent seen in centers and surgical procedures with historically higher rates of SSIs. 13 While the aforementioned small, retrospective, singlecentered studies provided hope that SSIs may be reduced early in the pandemic, [9][10][11]18 larger subsequent studies, including the findings herein, fail to demonstrate significant differences. Although counterintuitive, we observed no robust or statistically significant changes in SSI despite unprecedented changes in surgical workflow and PPE use.…”
Section: Discussionmentioning
confidence: 71%
“…Retrospective, single-centered studies from Italy, the United Kingdom, Germany, and Greece reported statistically significant reductions in SSIs following general surgery, cardiac surgery, neurosurgery, and colorectal surgery, respectively. [9][10][11]18 These findings are significant given that many of the surgical procedures performed following the COVID-19 shutdown were urgent/emergent in nature, conferring higher risk, while minor, elective procedures at low-risk of SSI were less commonly performed. A retrospective, propensity score matched study from India evaluated the risk of SSI following elective major oncologic surgery and reported that "increased compliance with hand hygiene, near-universal mask usage, and social distancing during the COVID-19 pandemic possibly led to 23% decreased odds of SSI in major oncologic resections."…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Not quantified J Orthop Surg Res Zeng et al [ 18 ] 1.0% 1.0% SSI orthopaedic surgery in Shenzen, China Increased HAI Am J Infect Control McMullen et al [ 19 ] Baseline 100% 157–279% Increase in urinary tract infections Am J Infect Control McMullen et al [ 19 ] Baseline 100% 327–420% Catheter-related bloodstream infections Hand hygiene compliances Am J Infect Control Moore et al [ 25 ] 46% compliance 56% compliance No data on HAI or SSI; 19 hospitals in USA Clin Microbiol Infect Israel et al [ 6 ] 46% compliance 80% compliance No data on HAI or SSI; Covid-Units in Jerusalem J Primary Care Comm Health Roshan et al [ 7 ] unreported baseline 80–95% No data on HAI or SSI. Mention of their reduction Am J Infect Control Wee et al [ 17 ] 85% 100% Reduction of selected HAI and of MRSA transmission …”
Section: Resultsmentioning
confidence: 99%
“…The SSI risk was significantly lower during the lockdown [ 16 ]. Similarly, a study in the field of cardiac surgery showed significantly lower rates of sternal wound infections in 493 patients operated during lockdown compared to patients with surgical intervention in the twelve months preceding the lockdown [ 17 ]. All authors attributed this to intensified precautions and additional SSI preventing measures including wear of protective equipment and surgical masks, reduction of present staff during surgery, shortened hospital stay, decontamination and isolation between patients, and restriction of visitors at the hospital.…”
Section: Discussionmentioning
confidence: 99%